Comparative time analysis of digital photogrammetry software using AI methods for design recovery in digital manufacturing - Paryanto, P.; Faizin, M.; Rusnaldy, R. (Jurnal Polimesin, 2025)
This research aimed to investigate the time efficiency of integrating traditional digital photogrammetry software compared to Artificial Intelligence (AI) in Reverse Engineering (RE). The investigation was conducted through a systematic comparison of the selected digital photogrammetry software and an AI-based method, using various objects for evaluation. Although high accuracy can be achieved with traditional photogrammetry software, the process is time-consuming, particularly for complex or large objects. Therefore, this research presents a timing analysis that demonstrates the efficiency advantages of AI-based methods over traditional digital photogrammetry software. The results showed that AI, by automating the reconstruction process, has the potential to reduce the time required for RE significantly. Moreover, the results of the 3D piston model using AI Google Colab™ were close to Agisoft Metashape, showing the potential use of alternative software as a solution in the RE process. These results suggested that AI-based methods could reshape the RE landscape, offering crucial efficiency gains for industries with rapid prototyping and just-in-time product development.